2015
DOI: 10.1111/cbdd.12545
|View full text |Cite
|
Sign up to set email alerts
|

Combined Molecular Docking, 3D‐QSAR, and Pharmacophore Model: Design of Novel Tubulin Polymerization Inhibitors by Binding to Colchicine‐binding Site

Abstract: Interference with dynamic equilibrium of microtubule-tubulin has proven to be a useful tactics in the clinic. Based on investigation into the structure-activity relationship (SAR) studies of tubulin polymerization inhibitors obtained from several worldwide groups, we attempted to design 691 compounds covering several main heterocyclic scaffolds as novel colchicine-site inhibitors (CSIs). Evaluated by a series of combination of commonly used computer methods such as molecular docking, 3D-QSAR, and pharmacophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
(126 reference statements)
0
13
0
Order By: Relevance
“…In several subsequents tudies, [43][44][45] cytotoxic properties of the compounds turned out to be due to their ability to inhibit the polymerization of tubulin.B ased on the results of docking, the authors draw conclusions aboutt he relationship between compound cytotoxicity and the way the compounds dock onto the receptor.This correlates well with the antitumor activity of these compounds. Other studies [46,[48][49][50][51] have been devoted to the modelling of pharmacophores, docking and virtual screening of varioust ubulin inhibitors. The authors use the obtained pharmacophore model of inhibition of tubulint od raw conclusions on the antitumor activity relative to new potentially active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In several subsequents tudies, [43][44][45] cytotoxic properties of the compounds turned out to be due to their ability to inhibit the polymerization of tubulin.B ased on the results of docking, the authors draw conclusions aboutt he relationship between compound cytotoxicity and the way the compounds dock onto the receptor.This correlates well with the antitumor activity of these compounds. Other studies [46,[48][49][50][51] have been devoted to the modelling of pharmacophores, docking and virtual screening of varioust ubulin inhibitors. The authors use the obtained pharmacophore model of inhibition of tubulint od raw conclusions on the antitumor activity relative to new potentially active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Combretastatin A-4 (CA-4), one of the best known and most potent combretastatin, has been reported as a promising cytotoxic agent, which strongly prevents tubulin polymerization by binding to the colchicine site. Combretastatin CA-4, a simple stilbene [ cis 1 (3,4,5-trimethoxyphenyl)-2-(30-hydroxyl-40-methoxy phenyl)-ethane] has been observed to vie for binding sites on tubulin in competition with colchicines 21 , 22 . CA-4 has therefore been considered as an appealing lead molecule for the improvement of antitumor drugs 23 .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] Research has focussed on developing novel colchicine site inhibitors (CSI), since the molecular structure of known colchicine-site inhibitors is less complex than that of taxanes and vinca alkaloids. 13 However, microtubule-destabilizing agents that bind at the colchicine-binding site and reached clinical trials had significant side effects, for example ZD6126 reached phase II trials for metastatic renal cell carcinoma but was withdrawn due to cardiotoxicity, 14 ABT-751 completed Phase I/II trials but adverse effects were revealed in Phase II. 15 Despite the great potential of combretastatins and their prodrugs, CA1P and CA4P, these also suffer from drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] Research has focussed on developing novel colchicine site inhibitors (CSI), since the molecular structure of known colchicine-site inhibitors is less complex than that of taxanes and vinca alkaloids. 13 However, microtubule-destabilizing agents that bind at the colchicine-binding site and reach clinical trials had significant side effects, for example ZD6126 is a phosphate prodrug of N-acetylcolchinol (NAC) releasing the drug after administration and in-vivo hydrolysis. NAC binds to the colchicine binding site and inhibits tubulin polymerization, reducing the proliferating immature endothelial cells that line the tumour blood vessels and consequently inducing tumour cell death.…”
Section: Introductionmentioning
confidence: 99%